Hendersonula toruloidea Nattrass. fungus on new host from Nandurbar district (M.S.) - B, Mangle B; B, Patil K (Journal of Experimental Sciences, 2013)
The present investigation report deals with the fungus collected from Nandurbar district, it is being new addition to the North Maharashtra region. Ipomea fistulosa Mort ex. Choisy is being reported as a new host substrate for Hendersonula toruloidea Nattrass.